A comparison of Colombian Pacific mangrove extent estimations: Implications for the conservation of a unique Neotropical tidal forest. (15th November 2018) - Mejía-Rentería, Juan C.; Castellanos-Galindo, Gustavo A.; Cantera-Kintz, Jaime R.; Hamilton, Stuart E.
Abstract: Environmental conservation, management, and policy rely on accurate scientific information and interpretation. Dramatic numbers related to the decline of a natural resource often get the attention of the media, and even the scientific community, and propagate through to wider society. Such headline-generating reporting of dramatic environmental loss scenarios can confuse and may result in poor decision making related to the application of funding priorities and policies driven by concerned scientists, environmental groups, and the public. Here we analyze the historical and current estimations of mangrove cover of a relatively pristine mangrove area of the Neotropics along the Colombian Pacific coast. Our comparison reveals highly differing estimates of mangrove coverage based on the methods used since the 1960's. As opposed to what is commonly claimed by some studies, and the media, mangrove cover in this region has likely remained relatively stable, at least over the last 15-years. Estimates constructed between 1966 and 1992 likely overestimate mangrove area due to the lack of high-resolution delineation methods, such as satellite imagery, and a lack of robust defined methodologies. Mangroves along the Pacific coast of Colombia, despite localized losses, likely remain one of the most well preserved tidal forests of the Neotropics. Future analyses of mangrove in this region need to treat with caution earlier estimates of mangrove cover that are likely overestimates based on dated technologies and undefined methodologies.